2014
DOI: 10.3945/ajcn.112.055517
|View full text |Cite
|
Sign up to set email alerts
|

Myofibrillar muscle protein synthesis rates subsequent to a meal in response to increasing doses of whey protein at rest and after resistance exercise

Abstract: Background: The intake of whey, compared with casein and soy protein intakes, stimulates a greater acute response of muscle protein synthesis (MPS) to protein ingestion in rested and exercised muscle. Objective: We characterized the dose-response relation of postabsorptive rates of myofibrillar MPS to increasing amounts of whey protein at rest and after exercise in resistance-trained, young men. Design: Volunteers (n = 48) consumed a standardized, high-protein (0.54 g/kg body mass) breakfast. Three hours later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
506
15
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 405 publications
(584 citation statements)
references
References 30 publications
39
506
15
11
Order By: Relevance
“…Because the mechanically sensitive pathways and the resistance exercise pathways are distinct, consuming essential amino acids following resistance exercise significantly activates mTORC1 above resistance exercise alone [103]. We have known for several decades that consuming essential amino acids in close proximity to resistance exercise can enhance the protein synthetic response in the skeletal muscle [104] and we now know that ~20g of high quality protein in the fasted [105] or fed [106] state is sufficient to saturate the protein synthetic response following resistance exercise in young men. Furthermore supplementation of protein during a program of resistance training is well proven to enhance lean mass/muscle gains [84].…”
Section: The Molecular Regulation Of Resistance Training Adaptation mentioning
confidence: 99%
See 1 more Smart Citation
“…Because the mechanically sensitive pathways and the resistance exercise pathways are distinct, consuming essential amino acids following resistance exercise significantly activates mTORC1 above resistance exercise alone [103]. We have known for several decades that consuming essential amino acids in close proximity to resistance exercise can enhance the protein synthetic response in the skeletal muscle [104] and we now know that ~20g of high quality protein in the fasted [105] or fed [106] state is sufficient to saturate the protein synthetic response following resistance exercise in young men. Furthermore supplementation of protein during a program of resistance training is well proven to enhance lean mass/muscle gains [84].…”
Section: The Molecular Regulation Of Resistance Training Adaptation mentioning
confidence: 99%
“…Several protein dose response studies have demonstrated that ~20g of high quality protein (egg white protein or whey protein) following resistance exercise with a small amount of muscle mass (single leg training) is sufficient to maximally stimulate MPS in the trained leg [105,106]. These studies have gone a long way to optimising post exercise nutrition.…”
Section: New/underexplored Areas In Protein Nutrition?mentioning
confidence: 99%
“…Indeed, acute human studies have observed activation of mTORC1 and its downstream targets (e.g., p70S6K, rpS6, and 4EBP‐1) following ingestion of mixed amino acids, and this is coupled with an increase in muscle protein synthesis (MPS) in the ensuing 60–120 min (Atherton, Etheridge et al, 2010; Koopman et al, 2006; Paddon‐Jones et al, 2004; Volpi, Kobayashi, Sheffield‐Moore, Mittendorfer, & Wolfe, 2003). Furthermore, when human skeletal muscle undergoes loading prior to amino acid ingestion this effect on mTORC1 signaling and MPS is potentiated (Moore, Atherton, Rennie, Tarnopolsky, & Phillips, 2011; Witard et al, 2014). The necessity for mTOR activation in mediating the MPS response to both amino acids and muscle loading is evidenced by the fact that in rodents, both stimuli fail to augment the synthetic response when in the presence of the mTOR inhibitor rapamycin (Anthony et al, 2000; Kubica, Bolster, Farrell, Kimball, & Jefferson, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis examining the efficacy of protein supplementation to increase lean body mass and strength after REX training revealed that protein supplementation significantly increased muscle mass and strength compared with placebo (Cermak et al, 2012). While the anabolic capacity of protein availability in human skeletal muscle is primarily attributable to the ingestion of essential amino acids (EAAs) and in particular the branched chain amino acid leucine, factors such as the dose (Moore et al, 2009a;Witard et al, 2013), source (Reidy et al, 2013;Tang et al, 2009;Tipton et al, 2004) and the timing/distribution of intake (Areta et al, 2013;Esmarck et al, 2001) also modulate the effectiveness for protein supplementation to augment muscle mass with REX. The 'anabolic' signalling pathways activated by REX and protein ingestion centre on intramuscular mTORC1 signalling (Kimball and Jefferson, 2010).…”
Section: Cellular Regulation Of Exercise Training Adaptation: a Primermentioning
confidence: 99%